2003
DOI: 10.3121/cmr.1.4.309
|View full text |Cite
|
Sign up to set email alerts
|

NSABP Breast Cancer Clinical Trials: Recent Results and Future Directions

Abstract: Over the past 40 years, the National Surgical Adjuvant Breast and Bowel Project (NSABP) has conducted several large, randomized clinical trials evaluating various aspects of surgical and adjuvant therapy in patients with operable breast cancer. Results from these trials have contributed significantly in reducing the extent of surgical procedures and in improving the outcome of patients with early-stage breast cancer. Furthermore, they have helped to establish standards of care for the surgical management of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 72 publications
3
45
0
1
Order By: Relevance
“…The difference of results between our study and the trial reported by Batra et al could be due to G-CSF administration in our study (22) . The limited data of the present study and data from large published trials support a combined doxorubicin and docetaxel regimen for neoadjuvant treatment (1,20,23) .…”
Section: Discussionmentioning
confidence: 94%
“…The difference of results between our study and the trial reported by Batra et al could be due to G-CSF administration in our study (22) . The limited data of the present study and data from large published trials support a combined doxorubicin and docetaxel regimen for neoadjuvant treatment (1,20,23) .…”
Section: Discussionmentioning
confidence: 94%
“…A recent meta-analysis of these trials concluded that there was no evidence to suggest that adjuvant clodronate therapy improves 5-year overall (HR, 0.75; 95% CI, 0.31-1.82), bone metastasis-free (HR, 0.68; 95% CI, 0.38 -1.23), or nonskeletal metastasis-free (HR, 0.89; 95% CI, 0.40 -1.98) survival in breast cancer patients [68]. Hopefully, a more definitive judgment on clodronate can be rendered when the eagerly awaited National Surgical Adjuvant Breast and Bowel Project B34 trial, which has accrued 3,000 patients, investigating adjuvant oral clodronate in patients with resected stage I-II breast cancer, has accumulated enough events to be reported, probably later this year [69].…”
Section: Prevention Of Bone Metastasesmentioning
confidence: 99%
“…pCR, pathological complete response; vinb, vinblastine; thi, thiotepa; met, methotrexate; FU, 5-flourouracil; adr, adriamycin; cyc, cyclophosphamide; epi, epirubicin; cis, ciplatin; doc, docetaxel; dox, doxorubicin; vinc, vincristine; vino, vinorelbine; tam, tamoxifen; pac, paclitaxel. 6,7 . 1493 patients with operable breast cancer were stratified by age, clinical tumor size, and clinical nodal status to preoperative versus postoperative administration of Adriamycin/cyclophosphamide (AC) q 21 days x four cycles.…”
Section: Neoadjuvant Chemotherapymentioning
confidence: 99%
“…Breast conservation therapy (BCT) rates were 67% versus 60%. Another landmark trial, NSABP B-27, enrolled 2411 patients in a randomized prospective trial to compare the efficacy of docetaxel in the preoperative versus postoperative setting after neoadjuvant AC x four cycles 7 . The patients were randomized into three groups ( Figure 1).…”
Section: Neoadjuvant Chemotherapymentioning
confidence: 99%